Contra a cordialidade: análise do conceito de Homem Cordial na obra de Sérgio Buarque de Holanda - Katz, Felipe Beltran (2018)
The present work tries to discuss the contributions of Sérgio Buarque de Holanda‟s (1902-1982) analysis as a thinker of Brazil. The focus shall be the concept of the heartily-man, a kind of synthesis of the Brazilian character. The heartily-man is neither benevolent nor peace-loving, as the word suggest, he is only capable of action through the heart, he expresses himself through emotions at the expense of reason. Therefore, the heartily-man is incapable of following the necessaries codes to the establishment of an impersonal and objective conduct. For Sergio Buarque, the conduct of the heartily-man prevents that, in Brazil, a clear definition between the public and private spheres exists. The Brazilian state, sometimes, becomes the extension of the interest of the powerful, who manage it to satisfy the whims of their extended families. Those that they not recognize as part of this extended family are abandoned or persecuted. Sérgio Buarque affirms that this heartily conduct needs to be abandoned, so democracy can arrive fully in Brazil. The state must be impersonal and collective, it must not submit itself to whim of the few and it must be inclusive. To abandon the heartily conduct is to put the state interests over the passions of the particulars and democratise the institutions